Gubernatorzy wojskowi w systemie polskiej administracji początków XIX w ieku - Marszałek, Piotr Krzysztof (Czasopismo Prawno-Historyczne, 2018)
In Polish literature on the subject, the military governor’s office is usually associated with the organisation of the administrative system that prevailed in the partitioning states (Poland’s Partitions 1791-1918). However, the governor’s office had already been known in Poland during the Duchy of Warsaw (1807-1815), when it was, like many other solutions of administrative and military law, imported directly from France. In the structure of Polish public organs, the office of governor was created for the first time during the Polish-Austrian war in 1809. Although no documents have survived from which we could learn of the competences of a Polish governor in those times, what is known is that the description of his authority followed closely the model set out by the French legislation. It was not before the Polish-Russian war in 1830-1831 that first attempts were made to independently set out the authority o f a governor of the Polish state, but even then, at least initially, the solutions set forth by the regime o f the Napoleonic decree were directly referred to and copied. In the second half of the 19th century, shortly before the collapse of the November Uprising, a draft describing the office and competences of a Polish governor was finally ready to be put forward for parliamentary discussion, but it was already too late for the Sejm to deal with it.